Entomopathogenic nematodes (Rhabditida: Steinernematidae and Heterorhabditidae) for the control of codling moth, Cydia pomonella (L.) under South African conditions - De Waal, Jeanne Yvonne (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScAgric (Conservation Ecology and Entomology))--Stellenbosch University, 2008.